Description of a New Haemogregarine, Haemogregarina sundarbanensis n. sp. (Apicomplexa: Haemogregarinidae) from Mud Turtle of Sundarban Regions, West Bengal, India - Molla, Sabir Hossen; Bandyopadhyay, Probir K; Gürelli, Gözde (Galenos Yayinevi, 2015)
The aim of this study was to provide a description of a new haemogregarine, Haemogregarina sundarbanensis n. sp., from mud turtles collected from Sundarban regions, West Bengal, India.The turtles were collected from fish markets near Canning, South 24-Parganas District, West Bengal. Thin blood films were prepared using the blood drawn from the head and feet. The blood films were then air-dried, fixed in absolute methanol, and stained with Giemsa.The erythrocytic stages could be differentiated into small and large forms. The young gamonts measured 7.896×3.469 μm, microgamonts measured 8.876×4.425 μm, and macrogamonts measured 8.919×4.272 μm. The cytoplasm of the macrogamonts was stained deep blue with Giemsa, and many metachromatic granules are found uniformly distributed. The oval or rounded nucleus was central in position and stained deep red with Giemsa stain, whereas in microgamonts, the nucleus was not at all compact but with a few dispersed chromatin granules.The prevalence of infection was found to be 33.3% (5/15). The infected erythrocytes reveal shape alteration, marginal and atrophic nucleus, and were larger than non-parasitized erythrocytes. The cytoplasm of the infected erythrocytes stained darker than that of the uninfected erythrocytes.
Keywords: Cell Nucleus; Erythrocytes; Coccidiosis; Schizonts; India; Azure Stains; Turtles; Eucoccidiida; Prevalence; Animals; Humans